(untitled) (Cambridge, 1996)
The Cambridge Illustrated History of Medicine examines, through popular and professional perception, the history and interrelation of disease, health and medicine over more than two thousands years. Readers can trace the chronological story of key developments and events in medical history from antiquity onwards, while at the same time engaging with the issues, discoveries and controversies that have beset and characterized medical progress. The book weaves a connective
Keywords: Medicine,Medicine history,Y học; History,Lịch sử